Simulation-based optimisation for material dispatching in Vendor-Managed Inventory systems. (17th December 2007) - Subramaniam, Ganesh; Gosavi, Abhijit
This paper examines a problem related to replenishing inventories at retailers in distribution networks operated under the paradigm of Vendor Managed Inventory (VMI). In the real world, complexity in analysing such systems arises out of numerous factors, including several random variables and a multitude of costs in the system. Much of the literature makes simplifying assumptions about these factors to develop tractable mathematical models. In this paper, we develop a simulation-optimisation approach that can accommodate most of these factors. In our experiments, our approach outperforms a heuristic used in a local industry and a heuristic developed from the newsvendor model.